Analysis of Digital Employment Contracts on Gig Economy Platforms: Between Flexibility and Exploitation - Firman Nurdiyansyah Sunandar; Ahmad Juaeni; Johannes Triestanto; Andri Herman Setiawan (International Journal of Law, Crime and Justice, 2025)
This research examines the legal framework governing digital employment contracts on gig economy platforms, with particular focus on the tension between operational flexibility and worker protection within the Indonesian legal context. The study employs comparative legal analysis methodology, exam-ining Indonesia's regulatory approach against international frameworks including the European Union's Platform Work Directive (2024), California's AB5 legislation, France's flexicurity model, and Spain's Rider Law. The research analyzes the employment status classification challenges faced by approximately 2.5 million Indonesian gig workers who operate within a legal gray area between traditional employment and genuine self-employment. The investigation reveals that Indonesia's current regulatory framework lacks comprehensive provisions addressing platform-mediated work relationships, creating significant legal ambiguity regarding worker rights and protections. Through comparative analysis, the study demonstrates that jurisdictions implementing presumption-based employment tests, such as California's ABC test, have successfully reduced misclassification by reversing the burden of proof onto hiring entities. The research identifies that the absence of clear classification criteria in Indonesian law undermines constitutional principles of social justice and equal protection as enshrined in Articles 27(2) and 28D(2) of the 1945 Constitution.The study concludes that Indonesia requires adaptive legislation that establishes rebuttable presumptions of employment for platform workers while maintaining appropriate flexibility for genuine entrepreneurial activities. The primary legal insight reveals that effective regulatory frameworks must in-corporate algorithmic transparency requirements, collective bargaining mechanisms, and social security provisions. The research recommends implementing a presumption-based classification system similar to the ABC test, coupled with mandatory platform engagement with elected worker representatives on tariffs and working conditions, thereby ensuring fundamental labor protections without stifling technological innovation.